A national survey of young women's beliefs about quitting indoor tanning: implications for health communication messages. Issue 6 (15th March 2018) - Bleakley, Amy; Jordan, Amy; Ellithorpe, Morgan E; Lazovich, DeAnn; Grossman, Sara; Glanz, Karen
Abstract: Indoor tanning is a risk factor for melanoma among young white women. Health communications can be an effective way of reaching this population and promoting behavior change. The purpose of this study was (i) to investigate the associations between intention to quit indoor tanning and attitudes, normative pressure, and efficacy about quitting, and (ii) to identify beliefs about quitting indoor tanning that can be used to design effective health communication messages to reduce skin cancer risk. A national online survey was conducted with 279 non-Hispanic white women ages 18–25 in the USA who are indoor tanners. The survey, based on the reasoned action approach, assessed intention, attitudes, norms, and efficacy and their corresponding underlying beliefs related to quitting indoor tanning, along with other known covariates. Data were collected in November/December 2015. Intention to quit indoor tanning was significantly associated with attitudes, specifically with the beliefs that it would "reduce damage to skin" (increased intention) and "make me less happy" (decreased intention). While self-efficacy was not related to intention to quit indoor tanning, injunctive normative beliefs were with key referent groups including mothers, friends, and romantic partners. Messages aimed at discouraging indoor tanning among young, non-Hispanic, white women should highlight the salient belief that quitting indoor tanning will reduce skin damage, counter the belief that it will make them less happy, and highlight key people who would approve of them quitting indoor tanning. Abstract : Health messages designed to discourage indoor tanning in young women should address beliefs related to skin damage and emotions associated with quitting.